Synthesis and characterization of perovskite-based materials for memory device application / Gregory Thien Soon How - Gregory Thien , Soon How (2021)
This project aims to study the resistive switching behaviour in memory devices using perovskites-based structures. A hybrid organic-inorganic lead halide perovskite was studied in this project, specifically methylammonium lead triiodide, CH3NH3PbI3 or MAPbI3 perovskite. The effect of the various counter electrodes in MAPbI3 perovskite was investigated by fabricating MAPbI3 perovskite on Indium Tin Oxide (ITO). Three commonly used electrodes which are Aluminium (Al), Silver (Ag), and Gold (Au) were thermally evaporated on top of the MAPbI3 perovskite layer. It was found that the ITO/MAPbI3/Al exhibits Resistive Random Access Memory (ReRAM) behaviour with SET voltage (VSET) of 4.5 V and RESET voltage (VRESET) of -1.3 V. On the other hand, ITO/MAPbI3/Ag and ITO/MAPbI3/Au reveals write-once-read-many (WORM) behaviour as ON process occurs at around 4.7 V and 4.0 V, respectively. Hence, it was proposed that the conductivity of iodide vacancies and the electrochemically active metal electrodes plays a role in determining ReRAM or WORM characteristics. Through this study, ReRAM based MAPbI3 perovskite memory device were selected by using TiO2 blend amounts of 0, 3, 5, and 10 mol% into the MAPbI3 layer. The ITO/MAPbI3-T5%/Al ReRAM device displays the highest improved VSET and VRESET values of 3.6 V and -1.1 V. This was owed to the refined grain size and film uniformity that aids in enhancing the mobility of iodide vacancies towards the ITO interface. Through this project, the importance of the electrode’s material in memory devices is crucial in varying resistive switching behaviour. Moreover, the novel design of a single layer TiO2 blend MAPbI3 perovskite opens new possibilities in simplifying ReRAM based devices.